Efficient aqueous As(III) removal by adsorption on thiol‐functionalized mesoporous silica. Issue 7 (27th January 2020) - Arencibia, Amaya; López‐Gutiérrez, María S; Arsuaga, Jesús M
Abstract: BACKGROUND: Arsenic pollution of water supplies is a global problem of environmental concern. Among inorganic species, trivalent arsenite, As(III), is the most toxic and difficult to remove. Conventional treatments usually involve the pre‐oxidation to pentavalent arsenic, As(V); however, this study is focused on the direct removal of aqueous arsenite species by selective adsorption. RESULTS: Sulfur‐containing adsorbents were prepared from mesostructured SBA‐15 silica by functionalization with propylthiol chains. The sulfur content of the synthetized materials, denoted as SBA‐15‐SH‐ x, reached 4 mmol g −1 . Kinetics and equilibrium batch experiments showed that all materials were excellent As(III) adsorbents, with maximum capacity as high as 0.46 mmol g −1, superior to literature values for comparable materials. The pH influence was significant and the best performance occurred at pH 8. A complementary pelletized material was designed and synthetized to explore the potential use of the adsorbents in the treatment of water streams polluted with arsenic through fixed‐bed column experiments. The breakthrough curves obtained in different operative conditions evidenced the viability of the process. CONCLUSIONS: SBA‐15‐SH‐ x materials evaluated in this work exhibited very good performance for aqueous As(III) removal by direct adsorption without previous oxidation to As(V). The suitability of the materials was demonstrated through kinetics, equilibrium, and fixed‐bed column adsorption experiments. © 2020 Society of Chemical Industry